Strategic human resources management and hotel performance - Luciano Aparecido Nascimento Machado; Deosir Flavio Lobo de Castro Junior; Tiago Savi Mondo; Elvis Silveira-Martins; Jean Carlos de Abreu (Tourism & Management Studies)
This study sought to verify strategic human resources management’s influence on hotel performance by analysing data on managers of hotels located in Grande Florianópolis, Brazil. Bibliographical research was conducted to provide a theoretical framework to support the analysis, and a descriptive methodology approach based on the positivist paradigm was applied. The proposed model was subjected to exploratory factor analysis, confirmatory factor analysis and structural equation modelling. The sample consisted of 70 hotel managers, and the data were collected with a closed-ended questionnaire. The results show that, of the 32 variables studied, 13 variables are connected to high performance in medium-sized hotels in Grande Florianópolis. In addition, the analyses confirmed the validity of the proposed model, in which strategic human resources management is directly related to hotel performance. The findings include that employee training and development, as well as workplace structuring, are strategic human resources management practices essential to achieving higher performance